2019
DOI: 10.1016/j.jpha.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly fluorescent carbon dots from lemon and onion juices for determination of riboflavin in multivitamin/mineral supplements

Abstract: In this work, lemon and onion biomasses commonly found in street markets are for the first time used to develop a facile, fast and low-cost one-step microwave-assisted carbonization method for synthesis of highly fluorescent carbon dots (CDs). The structure and optical properties of CDs were investigated by TEM, XRD, XRF, UV–Vis, FTIR, and fluorescence spectroscopy. CDs displayed satisfactory optical proprieties, a high quantum yield of 23.6%, and excellent water solubility, and the particle size was 4.23–8.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Wang et al 61 reported the formation of fluorescent CDs from milk by microwave cooking. Monte-Filho et al 62 revealed the production of CDs derived from lemon and onion after microwave treatment, which added further evidence to support the conclusion that microwave heating leads to the formation of CDs from food items.…”
Section: Microwave Heating Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Wang et al 61 reported the formation of fluorescent CDs from milk by microwave cooking. Monte-Filho et al 62 revealed the production of CDs derived from lemon and onion after microwave treatment, which added further evidence to support the conclusion that microwave heating leads to the formation of CDs from food items.…”
Section: Microwave Heating Methodsmentioning
confidence: 90%
“…35 Generally, food-borne CDs were amorphous, and X-ray diffraction patterns displayed a broad peak centered at about 20 . 62,[70][71][72] Notably, high-resolution transmission electron microscopy observations suggested the presence of lattice spacing in CDs in some cases. 69 These results reveal that CDs may have both amorphous and crystalline zones.…”
Section: Elemental Componentsmentioning
confidence: 99%
“…Moreover, CDs exhibited a good linear relationship between the fluorescent resonance energy transfer and the riboflavin concentration, suggesting the develop of an analytical method for the determination of riboflavin in multivitamin and mineral supplements. 288 Ahmadian-Fard-Fini et al were able to detect E. coli by a fluorescence sensor of CDs derived from grapefruit extracts and lemon. Fluorescence signals from various concentrations of E. coli-labeled CDs were observed.…”
Section: Biosensingmentioning
confidence: 99%
“…These fluorescent CDs demonstrated a 2–7 nm particle size with a 12% of quantum yield [ 91 ]. Another report by Filho et al reported fluorescent carbon dots with 23.6% quantum yield synthesized from lemon biomass and onion juices via a microwave method [ 92 ]. The synthesized CDs had a spherical morphology with higher monodispersity and a particle size of about 6.15 nm.…”
Section: Synthesis Of Carbon Dotsmentioning
confidence: 99%